Francophone Belgian cinema - Steele, Jamie (Traditions in world cinema., 2020)
Francophone Belgian Cinema offers an original critical analysis of filmmaking in an oft-neglected 'national' and regional cinema. The book draws key distinctions between the local, national, small national, regional and transnational frameworks in both representational and industrial terms.